Tampilan Berat Jenis, Bahan Kering Tanpa Lemak, Kadar Air dan Titik Beku Susu Sapi Perah Friesian Holstein pada Pemerahan Pagi dan Sore di CV Ben Buana Sejahtera Kecamatan Jatinangor Kabupaten Sumedang - Raden Febrianto Christi; Lia Budimulyati Salman; Nilawati Widjaja; Ajat Sudrajat (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2022)
The quality of good fresh milk is determined by the components of its composition. Water and milk dry matter are important constituents of milk components. Chemical properties are one part to determine the quality of milk. The purpose of the study was to determine the value of density, solid non fat, water content, and freez point of milk at morning and afternoon milking at CV Ben Buana Sejahtera farm, Jatinangor District, Sumedang Regency. The research method used is descriptive quantitative calculating the mean, standard deviation, and coefficient of variation with milk samples from 18 dairy cows with different lactation periods. 100 ml of milk was taken from each cow at different milking times, i.e. morning and afternoon, then put in a coolbox for testing of milk components such as density, solid non fat, water content, and freez point using lactoscan at the Dairy Production Laboratory. The results showed that the average density (1.026 VS 1.025), solid non fat (7.75% VS 7.42%), water content (85.75% VS 88.67%) and freez point (-0.5110C VS -0.4430C) milk in the morning and afternoon milking resulted in a difference. The conclusion showed that the component values ​​of density, solid non fat, water content, and freez point resulted in differences in the morning and afternoon milking. The quality of these components is still in normal condition in accordance with national standards. Keywords: density, solid non fat, water content, freez point, milk